Preferences in traits and management characteristics for dairy-beef animals from a survey of New Zealand farmers - Sneddon NW; Corner-Thomas RA; Kenyon PR; Brier D (Taylor and Francis Group on behalf of the Royal Society of New Zealand, 2025)
There are three parties involved in the expansion of dairy-beef or beef-on-dairy within New Zealand, they are namely, beef breeders, dairy farmers and beef finishers. Within these three groups, there are different requirements for an animal within each those industries. In 2022, Beef + Lamb New Zealand conducted a survey to collect responses from 121 respondents across these 3 parties, to gauge farmer preferences. The survey contained questions relating to the management of young cattle from birth through to weaning or sale (depending on management practice), and then from weaning or purchase through to finishing. All farmers were asked what traits they selected for in bulls, and what they based purchasing decisions on. The results showed a series of trends, related to breed choice, price and perceived benefit to their farming system. Calves from dairy cattle that had some Jersey genetics were seen as a finishing risk and were less attractive to finishing operations. There appeared to be a disconnect between the preferences of dairy and beef finishing operations, with sire selection having opposite selection criteria. The results of this survey indicate that work needs to be taken to align the goals of both beef finishers and dairy farmers.
Keywords: Dairy beef; survey; beef; breeding; selection